Ethyl Caffeate Ameliorates Collagen-Induced Arthritis by Suppressing Th1 Immune Response. (15th June 2017) - Xu, Shikui; Zuo, Aixue; Guo, Zengjun; Wan, Chunping
Abstract : The present study was designed to assess the antiarthritic potential of ECF in collagen-induced arthritis (CIA) and explore its underlying mechanism. Methods. In vitro, lymphocyte proliferation assay was measured by CCK-8 kit. In vivo, the therapeutic potential of ECF on CIA was investigated; surface marker, Treg cell, and intracellular cytokines (IL-17A and IFN- γ ) were detected by flow cytometry. Th1 cell differentiation assay was performed, and mRNA expression in interferon- γ -related signaling was examined by q-PCR analysis. Results. In vitro, ECF markedly inhibited the proliferation of splenocytes in response to ConA and anti-CD3. In vivo, ECF treatment reduced the severity of CIA, inhibited IFN- γ and IL-6 secretion, and decreased the proportion of CD11b+Gr-1+ splenic neutrophil. Meanwhile, ECF treatment significantly inhibited the IFN- γ expression in CD4+T cell without obviously influencing the development of Th17 cells and T regulatory cells. In vitro, ECF suppressed the differentiation of naive CD4+ T cells into Th1. Furthermore, ECF intensely blocked the transcriptional expression in interferon- γ -related signaling, including IFN- γ, T-bet, STAT1, and STAT4. Conclusion. Our results indicated that ECF exerted antiarthritic potential in collagen-induced arthritis by suppressing Th1 immune response and interferon- γ -related signaling.